Pushed monocanalicular intubation versus probing as a primary management for congenital nasolacrimal obstruction - Elsawaby EA (Dove Medical Press, 2016)
Emad Abdelaal Elsawaby, Rania Asem El Essawy, Sameh Hassan Abdelbaky, Yomna Magdy Ismail Department of Ophthalmology, Faculty of Medicine, Cairo University, Cairo, Egypt Purpose: Evaluation of efficiency, complications, and advantages of pushed monocanalicular intubation using Masterka® tube versus simple probing in patients with congenital nasolacrimal duct obstruction (CNLDO).Patients and methods: This is a case-controlled study that included 60 eyes (of 53 patients); 30 eyes underwent probing and 30 eyes intubation using the Masterka tube as a primary treatment for CNLDO. The children were aged between 6 months and 36 months at the time of surgery, with no previous nasolacrimal surgical procedure, and had one or more of the following clinical signs of nasolacrimal duct obstruction: epiphora, mucous discharge, and/or increased tear lake.Results: We defined success by absence of epiphora, mucous discharge, or increased tear lake 1 month after tube removal. The overall success rate in the probing group was 80%, while it was 83.3% in the intubation group.Conclusion: Pushed monocanalicular intubation is an effective method for treatment of CNLDO; it requires only mask inhalation anesthesia and could be considered as an appropriate alternative procedure with imperceptible complications. Keywords: epiphora, probing, intubation, monocanalicular, nasolacrimal